Quantitative Analysis of Energy Efficiency Indices in the Regions of the Russian Federation as Exemplified by Energy Consumption - Bogachkova, Lyudmila Yurievna; Khurshudyan, Shamam Garnikovna (International Journal of Energy Economics and Policy, 2015)
The Russian government has set the target of reducing energy intensity of the GDP by 40% over the period from 2007 to 2020. To solve the problem, energy conservation and increasing energy efficiency programs are implemented at the national, regional and municipal levels. The reduction in energy intensity can occur not only as a result of special measures to save energy resources, but for other reasons. The effectiveness of energy efficiency policies should be judged by such indicator which would reflect exactly technological efficiency. The current system of accounting energy efficiency in Russia has not yet handled this problem. In this article the energy intensity index of physical volume of the gross regional product was calculated and analyzed based on Rosstat data over 2005-2013 for the 80 regions of the Russian Federation. Additive decomposition of electricity consumption increment in the regions according to such major factors as economic activity, the structural and technological factors was performed. Keywords: Energy efficiency indicators; aggregated energy efficiency indices; energy intensity of the economy JEL Classifications: E02; G21; O13; Q43